Exploring the Impact of Emotional and Spiritual Intelligence on Job Satisfaction and Turnover Intention: Evidence from Mobile Telecommunication Companies in Ghana - Korankye, Benard; Amakyewaa, Evelyn (SEISENSE (PRIVATE) LIMITED, 2021)
Purpose- Several critical factors contribute to employees' satisfaction or an attempt to stay with an organization. This paper aimed to explore the impact of emotional and spiritual intelligence on job satisfaction and turnover intention among employees in the telecommunication companies in Ghana. Design/Methodology- A cross-section research design approach was adopted. A questionnaire was used to gather data from employees in MTN, Vodafone, and Airtel-Tigo in the Kumasi Metropolis Ghana through a simple random sampling approach. Statistical Package for Social Sciences (version 26) was to process data into tables and figures to help us undertake the descriptive, correlation, and multiple regression analysis. Findings- The study results indicate that emotional intelligence positively influences the job satisfaction and turnover intentions of employees. Spiritual Intelligence was found to influence job satisfaction positively but had a negative impact on the turnover intention of employees in mobile telecommunication companies. Practical Implications- The findings highlight the relevance of emotional and spiritual intelligence in promoting job satisfaction and turnover intention relative to emotional intelligence specifically. Furthermore, it would aid organizations in the sector with a huge workforce and large customer base to critically assess issues relating to emotional and spiritual intelligence to enhance job satisfaction and minimize the intent to leave the organization.